STRENGTHENING THE AGENCY CONSULTATION, MEDIATION AND LEGAL ASSISTANCE THROUGH DIRECT AND VIRTUAL CONSULTATION IN HIGHER EDUCATION IN THE EFFORT TO HELP PEOPLE CAN NOT AFFORD THE PERSPECTIVE OF DIGNIFIED JUSTICE - Sutrisno Sutrisno; Fauzul Aliwarman; Hervina Puspitosari; Anajeng Edhi Mahanani Esri (Surakarta Law and Society Journal, 2020)
Legal issues in the community are quite haunting, especially for specters. ordinary people who have no or less knowledge related to legal provisions. This ignorance is not without impact. Ignorance of legal provisions and readiness to deal with legal issues can reduce people's readiness in dealing with the law, or even create new legal problems, if because of ignorance it makes people who do not understand the law violate the law. This is what then drives the number of legal aid institutions ready to serve and provide legal assistance. Higher education legal aid institutions become laboratories that can, in real terms, utilize expertise in the field of law to disadvantaged communities in the realization of dignified justice. Besides that students can also practice becoming paralegals, and also can develop themselves in the field of legal assistance. The process of providing legal aid services can be done by assisting both litigation and non-litigation. So the need for strengthening the role of universities in providing legal assistance through legal aid agencies or institutions to help poor people. Keywords: Mediation and Legal Aid Consultation Board, Direct, Virtual.